The New Arab Gulf: Evaluating the Success of Economic Diversification in the UAE - Saima Shadab (15445406) (2023)
To date, the Gulf Cooperation Council (GCC) countries have remained oil-reliant, exposed to the vulnerabilities of the international oil price market. This study seeks to examine the role of economic diversification in the GCC, focusing on the UAE as a successful model. An empirical analysis is conducted to ascertain the short- and long-run relationship between diversification and economic growth in the UAE. Specifically, this study examines the role of export diversification in encouraging the UAE’s Gross Domestic Product (GDP) growth. The findings reveal that economic diversification fosters economic growth in the UAE both in the short and long run. The UAE serves as a successful model of economic diversification for the rest of the GCC countries as they share a congruent economic structure. Other Information Published in: Social Change and Transformation in the Gulf Region License: https://creativecommons.org/licenses/by/4.0 See chapter on publisher's website: https://dx.doi.org/10.1007/978-981-19-7796-1_25